Study of diet composition in sea cucumber intestines in Socah Waters, Bangkalan Regency - Fauziah Elys; Hidayati Dwi Ratna; Widodo Slamet; Omar Madiah Binti; Arifiyanti Nurul; Kurniyanto Ifan Rizky; Sulaiman Nur Iellyana Fasha Binti; Khairulanuar Aisya Afiqah Ajmal Binti Mohd (BIO Web of Conferences)
This paper aims to examine the understanding of the salt farmers regarding the Internet of Things (IoT) tool innovation and analyse their perceptions using five key innovation characteristics (Relative Advantage, Compatibility, Complexity, Trialability, and Observability). Internet of Things (IoT) has been considered as a key technology to assist in salt production improvements in Indonesia due to the continuing decline in production caused by climate change, especially in Madura Island. There was more than 75% decrease since 2019. In response, the Faculty of Agriculture at Trunojoyo University of Madura, Indonesia, in collaboration with Universiti Teknologi PETRONAS, Malaysia, conducted a socialization initiative for the salt farmer community in Pamekasan Madura on the importance of digitizing Internet of Things (IoT) technology. The socialization focused on an innovative product, the real-time monitoring tool 'Madura Smart Salt House (Mass),' specifically developed by UTP’s students. This tool aids in monitoring humidity, salinity levels, and weather on salt farms. A total of 20 salt farmers participated in the socialization. Pre- and post-survey were conducted to address participant understanding in before and after socialization around tool's functions and operations, followed by a survey on five key innovation characteristics. The data was analysed using descriptive quantitative (Frequency distribution). The evaluation results indicated that the salt farmers gained an increased understanding of the importance of IoT in salt farming. However, elements such as complexity, trialability, and observability have caused some hesitation among the farmers in adopting the innovation. Despite this, the farmers are confident that the innovation can offer relative advantages and possess characteristics that can be adapted to the existing culture of their salt farming practices.